Silence in Conversations About Advancing Pediatric Cancer - Rockwell, Sarah L.; Woods, Cameka L.; Lemmon, Monica E.; Baker, Justin N.; Mack, Jennifer W.; Andes, Karen L.; Kaye, Erica C. (Frontiers in Oncology, 2022)
Background and Objectives: Skillful use of silence by clinicians can support patient-centered communication. However, what makes a period of silence feel meaningful is not well understood. This study aimed to characterize profound, skillful silences during difficult conversations between pediatric oncologists, children with advancing cancer, and their families. Methods: We audio-recorded serial disease reevaluation discussions between pediatric oncologists, patients with high-risk cancer, and their families across 24 months or until death, whichever occurred first. Using an inductive process, we performed content analysis across all dialogue recorded at timepoints of disease progression to examine types of silence. Results: 17 patient-parent dyads with disease progression yielded 141 recorded conversations. Inductive coding yielded a layered typology of silence, including “intentional silence” (≥5 seconds), “profound silence” (≥5 seconds following receipt of difficult information, juxtaposed with statements of shared understanding, emotion, or enlightenment), and “stacked silence” (series of silences juxtaposed within dialogue). Intentional silence lasting ≥5 seconds occurred 238 times in 35/49 “bad news” recordings; nearly half (103/238) of these silences were identified as profound silence, in which silences appeared to create space for processing, allowed for questions to emerge, and synergized with empathic and affirmational statements. In most cases, profound silences involved the juxtaposition, or stacking, of multiple silences close together. Conclusions: Profound silences occur often during conversations about advancing pediatric cancer and share distinct characteristics. Opportunities exist to teach clinicians to use profound and stacked silences with intention during difficult conversations as a fundamental aspect of communication.